Profil Kesulitan Siswa dalam Menyelesaikan Masalah SPLDV ditinjau dari Computational Thinking Skill dan Self-Confidence - Mustika Khoirunnisa; Lukman El Hakim; Tian Abdul Aziz (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
This study aims to identify students’ difficulties in solving Two-Variable Linear Equation System (SPLDV) problems in terms of their computational thinking skills and levels of self-confidence. The study incorporates four indicators of computational thinking combined with students’ self-confidence levels to examine their patterns of difficulty more comprehensively. A qualitative case study approach was employed, involving two ninth-grade students from MTsN Muaradua who were selected based on the results of a self-confidence questionnaire and a computational thinking test. Data were collected through questionnaires, written tests, and semi-structured interviews. The findings show that students with high self-confidence were able to solve SPLDV problems across all four indicators through logical, reflective, and systematic steps. In contrast, students with low self-confidence experienced difficulties at the abstraction stage and particularly at the generalization stage when required to formulate a general equation from the obtained results. Low self-confidence led to hesitation in connecting relationships between variables and hindered reflective thinking. These findings indicate the need to strengthen affective aspects alongside the development of computational thinking in SPLDV learning.